S15 Changes in perioperative ards with time: a comparison of two trials. (15th November 2016) - Howells, PA; Aldridge, KA; Dancer, RCA; Tucker, O; Thickett, DR
Abstract : Introduction and objective: The BALTI-Prevention Trial1 translational sub-study (recruitment completed in 2011) and VINDALOO Trial2 (recruitment completed in 2015) both used oesophagectomy as a model for investigation of the pharmacological prevention of ARDS. The VINDALOO trial showed a lower ARDS incidence independent of the agents evaluated. Our objective was to characterise this difference. Methods: Databases from both trials were available and additional information was obtained retrospectively from hospital records. Analysis was performed using appropriate statistical tests. Results: There was a substantially higher ARDS incidence in BALTI-P compared to VINDALOO (RR 1.17 (1.08–1.28)) (Figure 1 ). There were more never (21 versus 7) and fewer current (12 versus 25) smokers in the VINDALOO group (p = 0.003). Perioperative risk scores did not differ between groups (P-POSSUM mortality p = 0.98, P-POSSUM morbidity p = 0.87, O-POSSUM p = 0.58), nor did use of neoadjuvant chemotherapy (p = 1.0). The incidence of serious complications (Clavien-Dindo score of four or more), was not different between the two groups (RR 1.15 (0.94–1.40)). Univariate analysis of the combined groups showed risk factors for ARDS not using regional anaesthesia (OR 3.2 (1.0–9.8) p = 0.038) and current smoking (OR 3.0 (1.1–8.3) p = 0.038). Conclusion: Smoking is an environmental risk factor for ARDS and changing patterns in smoking behaviour appear important in these perioperative cohorts. Other studies have demonstrated that aggregates of small but important changes in care can cumulatively make a significant difference to risk of nosocomial ARDS and our data suggests that this may have resulted in a reduction in perioperative ARDS in this group. Our study has demonstrated that ARDS incidence post oesophagectomy has fallen. In future, trials utilising oesophagectomy as a model of ARDS should consider selection of a defined higher-risk sub-set of patients. References: Perkins G, et al . The beta agonist lung injury trial prevention. A randomised controlled trial. Am J Respir Crit Care Med 2014;189 (6):674–683. Parekh D, et al . Vitamin D to prevent acute lung injury following oesophagectomy (VINDALOO): study protocol for a randomised placebo controlled trial. Trials 2013;14 (100). doi:10.1186/1745-6215-1114-1100.